2020
DOI: 10.31234/osf.io/zj6b4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health Impact of COVID-19: A global study of risk and resilience factors

Abstract: This study anonymously screened 13,332 individuals worldwide for psychological symptoms related to Corona virus disease 2019 (COVID-19) pandemic from March 29th to April 14th, 2020. A total of n=12,817 responses were considered valid with responses from 12 featured countries and five WHO regions. Female gender, pre-existing psychiatric condition, and prior exposure to trauma were identified as notable risk factors, whereas optimism, ability to share concerns with family and friends like usual, positive predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
2
17
0
4
Order By: Relevance
“…Worsening of psychiatric conditions is also associated with a higher risk of suicidal ideation, as demonstrated in the results of our study. 9,10…”
Section: Main Textmentioning
confidence: 99%
“…Worsening of psychiatric conditions is also associated with a higher risk of suicidal ideation, as demonstrated in the results of our study. 9,10…”
Section: Main Textmentioning
confidence: 99%
“…Previous studies have reported the importance of adequate procedures to detect early mental health worsening, 31 but have scarcely been conducted in the context of pandemics such as COVID-19.Identifying factors that are associated with worsening of psychiatric conditions has important implications for psychiatric prognostics and therapeutics. In our previous study, patients with prior psychiatric disease reported increased suicidal ideation 10. Understanding factors associated with psychiatric disease during a pandemic can help the patients, their family, and care-givers to screen and identify those at an increased risk of mental health crises situations such as suicide attempts.…”
mentioning
confidence: 94%
“…8 Worsening of psychiatric conditions is also associated with a higher risk of suicidal ideation, as demonstrated in the results of our study. 9,10 Psychiatric conditions constitute a significant burden on health-care systems. Previous findings have associated these conditions with increased rates of mortality, disability and reduced overall economic output.…”
mentioning
confidence: 99%
“…A few weeks into the COVID-19 crisis, a growing number of publications had already appeared on the adverse mental health effect, mostly in terms of depression and anxiety. Płomecka et al [1] documented the prevalence of psychological symptoms related to the COVID-19 pandemic among more than 13,000 individuals from 12 countries and five WHO regions worldwide (from March 29 to April 14, 2020). The study identified as notable risk factors: having female gender, a pre-existing psychiatric condition, or prior exposure to trauma, whereas optimism, the ability to share concerns with family and friends, having positive predictions about COVID-19, and daily exercise predicted fewer psychological symptoms.…”
Section: Introductionmentioning
confidence: 99%